Modeling and improvement of saddling a stepped hollow workpiece with a profiled tool - Markov, Oleg; Kosilov, Maksym; Panov, Volodymyr; Kukhar, Volodymyr; Karnaukh, Sergii; Ragulina, Nadiia; Bochanov, Pavlo; Rizak, Pavlo (Eastern-European Journal of Enterprise Technologies, 2019)
A new technological process of forging massive stepped hollow rings has been investigated based on modeling. This process implies the saddling of a hollow blank with a stepped deforming tool. We have devised a procedure of experimental modelling based on the law of geometrical similarity. The procedure makes it possible to establish regularities of change in the shape of a hollow workpiece and in the formation of surface defects while deforming with a stepped tool. The varied parameter was a relative height of the ledge (diameter ratio) of the original workpiece. Based on the research results, we determined the taper of rings, which forms during forging in line with a new technique. The study involved blanks made of lead and steel. Modeling allowed us to determine that the deformation with a stepped tool could lead to the emergence of taper on a ring. These results can be explained by the fact that the process of deformation of the ledge of a hollow workpiece is accompanied by a more intense deformation of the ring in a tangential direction than in the ledge, due to the difference in thicknesses of the stepped hollow workpiece. An increase in the degree of ledge deformation leads to an increase in its diameter. Macrostructural investigation of the wall of a stepped ring has allowed us to establish that the process of forging a stepped hollow workpiece with a ledge die leads to the formation of a fibrous structure that coincides with the profile of the stepped part. Such a location of fiber rules out the possibility of its cutting in the process of machining. Based on the results from experimental modeling, it was determined that it becomes possible to forge stepped hollow rings, which extends the technical possibilities of saddling massive parts for responsible purposes